Robotic or laparoscopic repeat hepatectomy after open hepatectomy: a cohort study - Birgin, Emrullah; Abdelhadi, Schaima; Seyfried, Steffen; Rasbach, Erik; Rahbari, Mohammad; Téoule, Patrick; Reißfelder, Christoph; Rahbari, Nuh Nabi (Surgical endoscopy and other interventional techniques, 2024)
Repeat hepatectomies are technically complex procedures. The evidence of robotic or laparoscopic (= minimally invasive) repeat hepatectomies (MIRH) after previous open hepatectomy is poor. Therefore, we compared postoperative outcomes of MIRH vs open repeat hepatectomies (ORH) in patients with liver tumors after previous open liver resections.
Gesehen am 07.02.2024